Pengaruh Penggunaan Rak Rangkaian dan Self Confidence terhadap Hasil Belajar Kelistrikan Bodi Siswa SMK - Muhammad Yusufrakadhinata; Marji Marji; Syarif Suhartadi (Pascasarjana Universitas Negeri Malang, 2021)
Abstract: The purposes of the research is to determine: 1) the differences in learning outcomes of body electricity between groups using safety-based circuit racks (RRBS) and conventional circuit racks (RRK), 2) the differences in learning outcomes in body electrical between groups of students who have low, medium and high self-confidence. Data analysis used Two Ways ANOVA. The sample of this research is class XI TKR 1 & 4. The results of this study are 1) there is a significant difference in the learning outcomes of body electricity between the groups using RRBS and RRK. 2) there is a significant difference in the learning outcomes of body electricity between groups of students who have low, medium and high self confidence. Abstrak: Penelitian ini bertujuan untuk (1) mengetahui perbedaan hasil belajar kelistrikan bodi antara kelompok yang menggunakan rak rangkaian berbasis safety (RRBS) dengan rak rangkaian konvensional (RRK); (2) mengetahui perbedaan hasil belajar kelistrikan bodi antara kelompok siswa yang mempunyai low, medium and high self confidence. Analisis data menggunakan Anova 2 jalur. Sampel penelitian ini adalah kelas XI TKR 1 dan 4. Hasil dari penelitian ini adalah (1) ada perbedaan yang  signifikan hasil belajar kelistrikan bodi antara kelompok yang menggunakan RRBS dengan RRK. (2) ada perbedaan yang signifikan hasil belajar kelistrikan bodi antara kelompok siswa yang mempunyai low, medium and high self confidence.